Characterization and comparison of human limbal explant cultures grown under defined and xeno-free conditions. (November 2018) - Brejchova, Kristyna; Trosan, Peter; Studeny, Pavel; Skalicka, Pavlina; Utheim, Tor Paaske; Bednar, Jan; Jirsova, Katerina
Abstract: Human limbal epithelial cells (LECs) intended for treatment of limbal stem cell deficiency are commonly cultivated on a 3T3 feeder layer with complex culture medium supplemented with fetal bovine serum (FBS). However, FBS is a xenogeneic component containing poorly characterised constituents and exhibits quantitative and qualitative lot-to-lot variations. Human limbal explants were plated on untreated or fibrin coated plastic plates and cultured in two non-xenogeneic media (supplemented with either human serum or platelet lysate only). Our aim was to find out whether the characteristics of harvested LEC cultures are comparable to those of LEC cultivated in the gold standard - FBS-supplemented complex medium. The growth kinetics, cell proliferation, differentiation, stemness maintenance, apoptosis and contamination by other cell types were evaluated and compared among these conditions. In all of them LECs were successfully cultivated. Stemness was preserved in both xeno-free media. However, cells cultured with human serum on the fibrin-coated plates had the highest growth rate and cell proliferation and very low fibroblast-like cell contamination. These data suggest that xeno-free cell culture conditions can replace the traditional FBS-supplemented medium and thereby provide a safer protocol for ex vivo cultured limbal stem cell transplants. Highlights: Both non-xenogeneic media maintain a high number of stem cells and low level of apoptosis in LEC cultures on both substrates. hSM combined with fibrin scaffold yields higher growth rates and proliferation of LEC cultures compared to hPLM. Fibroblast-like cell contamination of LEC cultures is less pronounced in hSM combined with fibrin scaffold than in hPLM. The growth onset and harvest of LEC cultured in hSM on fibrin scaffold are comparable with that of COM.